1999
DOI: 10.1176/ps.50.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Changes Among Patients With Obsessive-Compulsive Disorder in a Partial Hospitalization Program

Abstract: Thirty treatment-resistant patients with a primary DSA-IV diagnosis of obsessive-compulsive disorder were assessed at admission to and discharge from a partial hospitalization program to determine whether improvement in symptoms of the disorder was associated with improvements in patients' quality of life. Symptom severity was measured using the Yale-Brown Obsessive Compulsive Scale (YBOCS). Quality of life was measured using Lehman's Quality of Life (QOL) scale, which includes several objective and subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 8 publications
1
32
0
3
Order By: Relevance
“…However, some studies report that the decrease in productivity and quality of life of severely ill and/or treatment-resistant anxiety patients was comparable to those of schizophrenics. 10,11 Anxiety Disorders Association of America estimates the costs to be over 42 billion dollars per year comparable to those of stroke and cardiovascular disorders. 12 …”
Section: Introductionmentioning
confidence: 99%
“…However, some studies report that the decrease in productivity and quality of life of severely ill and/or treatment-resistant anxiety patients was comparable to those of schizophrenics. 10,11 Anxiety Disorders Association of America estimates the costs to be over 42 billion dollars per year comparable to those of stroke and cardiovascular disorders. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The extant research suggests that significant but small improvements in QOL occur after cognitive-behavioral therapy or pharmacological treatment for OCD [e.g., Stewart et al, 2005;Tenney et al, 2003]. Overall improvements in QOL typically are unrelated or are related weakly to symptom reduction [e.g., Bystritsky et al, 1999]. Bystritsky et al [2001] compared psychosocial deficits and QOL impairments in patients with OCD to patients with schizophrenia before and after their respective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Such insight helps the therapist create a basis to construct an adequate treatment strategy for the patient. Some studies reported that QoL improves over the course of psychotherapy and psychopharmacological treatment in OCD [9][10][11][12][13] . However, there is some evidence that QoL increases independent of symptom improvement.…”
Section: Introductionmentioning
confidence: 99%